Temporal variations of soil NO and NO2 fluxes in two typical subtropical forests receiving contrasting rates of N deposition. (15th February 2022) - Ke, Piaopiao; Kang, Ronghua; Avery, Loreena K.; Zhang, Jiawei; Yu, Qian; Xie, Danni; Duan, Lei
Abstract: Soils have been widely acknowledged as important natural sources of nitric oxide (NO) and meanwhile sinks of nitric dioxide (NO2 ). High nitrogen deposition across South China could potentially result in large NO emissions from subtropical forests soils there. In this study, the dynamic chamber method was applied to monitor NO and NO2 fluxes at two subtropical forest sites in South China, namely "Qianyanzhou" (QYZ) and "Tieshanping" (TSP). Chronically higher N deposition occurred at TSP than that at QYZ. Besides soil water filled pore spaces (WFPS) and temperature, ambient NO concentration could also possibly be important in regulating temporal NO emissions, especially in the winter. For both sites, the optimum soil temperature was above 25 °C, while the optimum WFPS for NO release at QYZ was higher (65–70%) than that at TSP (<23%). Moreover, heavy rainfall could trigger NO emission pulses from moist soils at QYZ, while rainfall-induced NO pulses were only observed after a long drying period at TSP. Distinctly different contents of mineral nitrogen and soil moisture conditions between the two sites might induce the divergent preference of WFPS and responses to rainfall. The cumulative soil emission of NO reached 0.41 ± 0.01 and 0.76 ± 0.01 kg N ha −1 yr −1 at QYZ and TSP, contributing to 2.5% and 1.4% of the annual throughfall N input, respectively. At both sites, NO2 were mainly deposited to soils, accounting for 2% and 21% of soil-emitted NO at QYZ and TSP, respectively. The observed annual NO emissions at these two sites were larger than the median values observed for tropical and temperate forests and unfertilized croplands. Higher N deposition could induce larger NO emission potential, while soil temperature and pH might also be important in regulating regional soil NO emissions as N-loss from subtropical forests. Graphical abstract: Image 1 Highlights: Soil NO emissions were 0.41 and 0.76 kg N ha −1 yr −1 at two subtropical forests. NO2 fluxes were bi-directional above subtropical forest soils. Ambient NO concentration contributed to regulating variability of soil NO emissions. N deposition induce larger potentials of soil NO emissions.